EFFECT OF LEADERSHIP AND ORGANIZATIONAL COMMUNICATION ON ORGANIZATIONAL CULTURE AND THEIR IMPACT ON EMPLOYEE PERFORMANCE AT PT. WIRA KHARISMA PROPERTY - Siska Yunanti; Rizka Wahyuni Amelia; Lina Nofiana (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The purpose of this research is to know the partial and simultaneous influence of leadership and organizational communication to organizational culture, to know the influence of organizational culture on employee performance and to know the partial and simultaneous influence of leadership and organizational communication on employee performance.This research is associative with quantitative approach. Population in this research is all employees of PT. Wira Kharisma Property, while the sample used in this study as many as 100 respondents. Technique of collecting data by questionnaire, and technique of data analysis using instrument test, classical assumption test, path analysis, t test and f count test. The results showed, There is influence between leadership on organizational culture at PT. Wira Kharisma Property. This can be proved by the coefficient value of the path of 0.466 and the value of 5.499> t table 1.984 with significant 0.000 t table 1.984 with significant 0.002 F table 3.09 with significant 0.000 t table 1.984 with significant 0.000 t table 1.984 with significant 0.019 t table 1.984 with significant 0,000 F table 3.09 with significant 0.000